The influence of pressure and dissolved gases in petroleum on the efficiency of wax deposition inhibitors - Vieira, Lenise; Buchuid, Maria; Lucas, Elizabete (Publishing House of Lviv Polytechnic National University, 2008)
Evaluations of wax inhibitors carried out in laboratories are generally performed on stabilized oil samples, that is, without the presence of natural gas and at atmospheric pressure. Therefore, the effects of two important factors that influence wax solubility – the light fractions and temperature – are not considered, and the results may not reflect what really happens in production lines and facilities. This work evaluates the efficiency of two wax inhibitors based on ethylene copolymer and vinyl acetate, at four concentrations, in a sample of paraffin oil in the presence of light fractions and under pressure. The parameter employed in the evaluation was the wax appearance temperature (WAT), or the cloud point, determined by high-pressure differential scanning calorimetry. The gas used was a mixture of eight components and the tests were run at three pressures. In general, the inhibitors had little influence on the cloud point and a pronounced effect on the pour point and viscosity. In this case it was possible to observe changes in the WAT with both wax inhibitors in the tests conducted at atmospheric pressure up to 150 bar and in the presence of the multi-component gas mixture, suggesting that one of the mechanisms through which wax deposition inhibitors work is polynucleation. У роботі під тиском та при чотирьох різних концентраціях проведено оцінку дії двох парафінових інгібіторів на основі кополімеру етилену і вінілацетату для парафінистої нафти, що містить світлі фракції. Параметром оцінювання була температура появи парафіну (WAX), тобто температура помутніння, яка визначалась диференційною скануючою калориметрією під високим тиском. Використано газ, що складається з восьми компонентів. Дослідження проведені при трьох різних тисках. Встановлено, що інгібітори незначно впливають на температуру помутніння, але мають помітний вплив на температуру застигання та в’язкість. Встановлено, що зміни у WAX спостерігались для обох інгібіторів як при атмосферному тиску і до 150 бар, так і в присутності багатокомпонентної газової суміші, що дозволяє припустити поліциклічний механізм дії інгібіторів.
Вплив тиску і розчинених у нафті газів на ефективність інгібіторів парафінових відкладів
Keywords: high pressure mDSC; viscosity; crude oil; paraffin; wax crystallization; deposition inhibitors; диференційна скануюча калориметрія під високим тиском; в’язкість; сира нафта; парафін; кристалізація парафіну